Nis money institutions in the banking system of the Kingdom of Yugoslavia - Becić Ivan M. (Baština, 2023)
At the end of the 19th and the beginning of the 20th century, a large number of local financial institutions were established in the Kingdom of Serbia. Nis was the second largest city in Serbia, and at the same time an important traffic and strategic center. By the end of the 19th century, three banks were established in Nis, and by the beginning og the WWI, their number had rise to eight. It was characteristic of almost all these financial institutions that they were the owners of mills, brick factories, textile factories, leather factories, and warehouses. The beginning of the WWI and the occupation of Serbia caused great material losses to the banks in Nis, especially from the Bulgarian army, which took away all movable property after the retreat. Among the human victims was a relatively large number of shareholders, board members and officials of financial institutions. With the end of the war, the banks could not immediately resume their operations, and for the first two years mostly collected their assets, and the two Nis banks could not continue their operations due to the high degree of damage. The remaining banks, accustomed to working with nonbanking businesses, continued this practice and invested in trade and industry. The chronic need for capital influenced the establishment of six more banks in Nis after the war. However, by 1925, two banks went bankrupt, and this happened to two more financial institutions by the end of the decade, so that the banking crises in the Kingdom of Yugoslavia was met by eight Nis banks. Due to the great crisis, business in the 1930s was extremely limited. Two financial institutions in Nis were under protection, and two managed to operate successfully until the outbreak of the WWII on the territory of Yugoslavia, when all normal work of banks was impossible.